Managing missed compartment syndrome in the upper extremity: A review of strategies and challenges - Brian Kwan; Hillary Rolfs; Esther Kuan; Ashley Lamb; Emily Benson; Damayea Hargett (Trauma Case Reports)
Compartment syndrome in the upper extremity, particularly when missed or delayed in diagnosis, poses significant clinical challenges and long-term consequences. Diagnostic challenges include varied clinical presentations and the frequent occurrence in patients who are found down with altered mental status due to drug overdose, complicating timely recognition. Emergent fasciotomy remains crucial in acute cases. However, controversies persist regarding the necessity, timing, and extent of fasciotomy in patients with missed compartment syndrome in the upper extremity. We discuss three cases of patients who presented after prolonged compression of the upper extremity and their respective outcomes. Additionally, this review synthesizes current literature and clinical experiences to delineate optimal management strategies for this devastating orthopedic emergency.